Evidenzbasierte Kriterien zur (provisorischen) Diagnose bei LBP - Vielitz, Arne (manuelletherapie, 2020)
Vining RD, Shannon ZK, Minkalis AL et al. Current Evidence for Diagnosis of Common Conditions Causing Low Back Pain: Systematic Review and Standardized Terminology Recommendations. J Manipulative Physiol Ther 2019; 42: 651–664. doi: 10.1016/j.jmpt.2019.08.002